Maternal and Perinatal Outcomes of Pregnant Patients with Coronavirus Disease 2019: Data from a University Hospital Setting in Tirana, Albania, May 2020 to November 2021 - Enkeleda Prifti; Najada Como; Enxhi Vrapi; Alketa Hoxha Qosja; Evelina Kreko; Nevila Kryemadhi; Elizana Petrela; Irsida Mehmeti; Genci Hyska (Hindawi Limited, 2023)
Scientific evidence suggests an increased risk of maternal and obstetric complications in pregnant patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study is aimed at evaluating perinatal and maternal outcomes among patients with coronavirus disease 2019 (COVID-19) in a university hospital setting. This was a prospective cohort study of 177 pregnant women with confirmed SARS-CoV-2 infection at a tertiary hospital between May 2020 and November 2021. Both symptomatic and asymptomatic women with a positive reverse transcription-polymerase chain reaction test result at any time during pregnancy were included in this study. For the purpose of this study, we classified COVID-19 cases into two groups: mild and severe cases. The two groups were then compared to predict how the clinical presentation of COVID-19 affected adverse maternal and perinatal outcomes. Gestational age≥20 weeks at the time of infection was significantly associated with the occurrence of severe forms of the disease (relative risk (RR) 3.98, p=0.01). Cesarean section was the preferred mode of delivery, with 95 women (62.1%) undergoing surgery. A total of 149 neonates were delivered to women who had confirmed SARS-CoV-2 infection at any time during the course of pregnancy of which thirty-five (23.5%) were admitted to the neonatal intensive care unit (NICU). Severe forms of COVID-19 increased the risk of premature delivery (RR 6.69, p<0.001), emergency cesarean delivery (RR 9.4, p<0.001), intensive care hospitalization (RR 51, p<0.001), and maternal death (RR 12.3, p=0.02). However, severe forms of SARS-CoV-2 infection are not directly responsible for low birth weight or the need for neonatal resuscitation. Our findings suggest that pregnant women presenting with severe COVID-19 disease are at an increased risk of adverse maternal and perinatal outcomes, such as premature delivery, cesarean section, admission to the ICU, and maternal death. Infection after the 20th week of gestation increases the risk of developing severe forms of the disease.